How to Improve Academic Resilience? Involving Family Functioning - Uswatun Hasanah; Nada Nafisah; Elmanora; Maya Oktaviani; Vania Zulfa (Migration Letters, 2023)
In education, students experience various academic obstacles, which causes a decrease in student achievement. Therefore, students must resolve those problems to develop their academic quality. So, students need academic resilience. Academic resilience is a condition built from the individual, family, and environmental factors. This study aims to analyse the effect of family functioning on students’ academic resilience. The research took place from May to June 2022. The sample in this study was selected using the multistage sampling method and involved 131 students from a public school. Measuring family functioning uses an instrument consisting of 24 statement items based on the dimensions of problem-solving, communication, and personal goals. At the same time, the measurement of academic resilience uses an instrument consisting of 30 statement items based on persistence, self-reflection, adaptive seeking of help, negative influences, and emotional responses. Data analysis used descriptive and inferential statistics, namely simple linear regression tests. The results showed that family functioning significantly positively affected students’ academic resilience (β=0.708, p<0.00). These results indicate that the higher the family functioning, the higher the student’s academic resilience. The coefficient of determination obtained is 21.4%, meaning family functioning affects students’ academic resilience.